2018
DOI: 10.1186/s12887-018-1294-5
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration error and contributing factors among pediatric inpatient in public hospitals of Tigray, northern Ethiopia

Abstract: BackgroundMedication administration error is a medication error that occurs while administering a medication to a patient. A variety of factors make pediatrics more susceptible to medication errors and its consequences. In low-income countries, like Ethiopia, there is no sufficient evidence regarding medication administration error among pediatrics. The aim of this study is, therefore, to determine the magnitude and factors associated with medication administration error among pediatric population.MethodsA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 15 publications
3
68
5
1
Order By: Relevance
“…Omitted drug error: is failure to administer a prescribed medication, patient error: when a medication of one patient is wrongly given to another patient, dose error: when prescribed quantity is not administered, medication error: when another medication is administered to the patient other than the prescribed, time error: when there is a difference of greater or less than 30 min between the ordered time and administered time, unauthorized drug error: medication administered was not authorized by the prescriber, technique error: the nurse performs less than 50% among the procedure put at the technique competency checklist for medication administration, route error: when medication is administrated in different route other than the ordered actual route, documentation error: When medication that is administered to the patient is not documented in medication administration record sheet. [17][18][19][20]36,37 This review targets all nurses in Ethiopia. Studies, in which participants were drawn from overall health care professionals, were excluded; unless the studies were separately documented for nurses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Omitted drug error: is failure to administer a prescribed medication, patient error: when a medication of one patient is wrongly given to another patient, dose error: when prescribed quantity is not administered, medication error: when another medication is administered to the patient other than the prescribed, time error: when there is a difference of greater or less than 30 min between the ordered time and administered time, unauthorized drug error: medication administered was not authorized by the prescriber, technique error: the nurse performs less than 50% among the procedure put at the technique competency checklist for medication administration, route error: when medication is administrated in different route other than the ordered actual route, documentation error: When medication that is administered to the patient is not documented in medication administration record sheet. [17][18][19][20]36,37 This review targets all nurses in Ethiopia. Studies, in which participants were drawn from overall health care professionals, were excluded; unless the studies were separately documented for nurses.…”
Section: Methodsmentioning
confidence: 99%
“…20,37 Type and magnitude of MAEs Regarding the types of MAEs, though the proportion of MAEs is varied for each type of error based on the number of rights used as a reference 26,27 definitions 46 and phases of medication administration process; [11][12][13] in this study, around thirteen different types of MAEs were identified such as: wrong route, wrong time, wrong patient, wrong dose, wrong drug, error of omission, wrong rate, documentation errors, duration error, technical error, unauthorized and without hand washing/change glove. [17][18][19][20]24,36,37 In each included study, five 18 up to eight 37 different types of MAEs were identified; though, one study reported only the overall result. 45 The most frequently reported type of MAEs were wrong time and wrong dose errors (n=6.7).…”
Section: Figure 1 Flowchart Of the Studymentioning
confidence: 99%
See 3 more Smart Citations